2002
DOI: 10.1016/s0248-4900(02)01179-6
|View full text |Cite
|
Sign up to set email alerts
|

New magnet‐sensitive structures in bacterial and archaeal cells

Abstract: The objects of the investigation were: distribution of intracellular magnet-sensitive structures among different taxonomic groups of prokaryotes, localisation and organisation of the magnet-sensitive inclusions (MsI) in cells. The MsI were discovered in representatives of both prokaryotic domains (Bacteria and Archaea), 2 kingdoms and 7 orders of bacteria. They were some amorphous or non-crystalline globules with the electron-transparent centre surrounded with an electron-dense homogenous matrix. The magnetic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
34
0
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 24 publications
1
34
0
2
Order By: Relevance
“…Vainshtein et al (57) identified magnet-sensitive particles in Ectothiorhodospira shaposhnikovii which were rich in Fe but did not contain sulfur. In a separate study, Vainshtein et al (56) found magnet-sensitive inclusions of various types in prokaryotic cells of diverse phylogenies when they were grown in medium containing 1 mM iron, suggesting some kind of detoxification function. The inclusions were not ordered crystals and incorporated various other unspecified organic compounds.…”
Section: Discussionmentioning
confidence: 98%
“…Vainshtein et al (57) identified magnet-sensitive particles in Ectothiorhodospira shaposhnikovii which were rich in Fe but did not contain sulfur. In a separate study, Vainshtein et al (56) found magnet-sensitive inclusions of various types in prokaryotic cells of diverse phylogenies when they were grown in medium containing 1 mM iron, suggesting some kind of detoxification function. The inclusions were not ordered crystals and incorporated various other unspecified organic compounds.…”
Section: Discussionmentioning
confidence: 98%
“…[4][5][6][7]9,[32][33][34][35][36][37][38][39][40] However, as already mentioned, for the first time BMNPs have been revealed in MTB that are characterized by the ability to "taxi" or navigate under a geomagnetic field. That is why historically the idea of magnetotaxis was transformed into an 59 dolphins, whales, 60 and humans.…”
Section: Physicochemical Properties Of Bmnps Bmnps In Mtb Magnetosomesmentioning
confidence: 99%
“…As a rule, BMNPs in multicellular organisms vary in shape, size, and other properties, and are not enclosed in magnetosome vesicles. 39,68 In archaea, in which the surroundings of BMNPs have been adequately investigated, magnet-sensitive inclusions have been found, which are surrounded by a homogeneous matrix with organic (mainly protein) components. 39 The absence of vesicles or a similar organic matrix consisting of protein filaments around magnetite BMNPs 68 has also been observed in human cells.…”
Section: Physicochemical Properties Of Bmnps Bmnps In Mtb Magnetosomesmentioning
confidence: 99%
See 2 more Smart Citations